O-B04 The effect of high fat diet and subsequent intentional weight loss on tumour burden in an animal model of spontaneous endometrial cancer. (16th December 2021) - Sinclair, Piriyah; Wilkinson, Michael; Conroy, Emer; Downey, Paul; Gallagher, William; Docherty, Neil; Roux, Carel le; Brennan, Donal
Abstract: Background: Obesity drives endometrial cancer (EC). Metabolic surgery (MS) induces sustained weight loss, reduces EC risk and has been shown to reverse histological changes of endometrial hyperplasia. One mechanism is increased GLP-1 post surgery. Few interventional studies have been conducted in the BDII/Han rat; an animal model of spontaneous EC. This study aimed to examine whether high fat diet (HFD) and weight gain, as well as subsequent intentional weight loss using Liraglutide (a GLP-1 receptor agonist) alters EC tumour biology and burden in the BDII/Han rat. A rat imaging protocol was validated to assess development and longitudinally track tumours. Methods: An imaging protocol was developed and validated. 7 BDII/Han rats were fed normal chow (NC) and 8 weight-matched rats fed HFD from 3 months of age. Longitudinal PET-CT was conducted at 7, 9, 12 and 15 months. Abdominal visceral fat was analysed from L1-L5 on CT. Subsequently, an intervention study compared the 8 HFD-Control rats to 8 weight-matched HFD-fed rats treated with Liraglutide from 12-15 months. PET-CT was used to assess disease progression. Analysis of histological, immunohistochemical and transcriptomic parameters were used to compare cohorts. All rats were euthanased aged 15-months. Imaging was correlated with necropsy findings and histopathology. Results: HFD rats had more abdominal fat on CT imaging (8.6cm3±0.7vs4.0cm3±0.6;p<0.0005) and 10% higher body-weight than NC rats (232.5g±4.9vs209.4g±2.0;p=0.001) at the study end. Histopathology demonstrated EC in 57%(n = 4) of NC and 50%(n = 4) of HFD rats. PET-CT was 87.5% sensitive and 86% specific. Liraglutide induced significant reduction in final body weight (208.3g±5.7vs232.5g±4.9;p=0.006) and abdominal fat on CT compared to controls (4.4cm3±0.4vs8.6cm3±0.7; p=0.0001). 2 tumours were identified in the Liraglutide group (25%) compared to 4 in the control group (50%). GLP-1 receptor expression was not detected in benign or malignant BDII/Han uterine tissue. Conclusions: This study has established a safe, sensitive and specific imaging protocol for longitudinal assessment of EC progression in BDII/Han rats. The HFD intervention used did not accelerate EC burden. However, it did create an obese phenotype and gave new information on the pathological variations of EC in the BDII/Han rat. Intentional weight loss from Liraglutide halved EC burden compared to controls in this study. An absence of GLP-1R expression may suggest weight loss dependent mechanisms. This novel pilot study is a foundation for future studies assessing the effect of intentional weight loss using metabolic surgery in obesity-related cancer.